NEW TECHNOLOGIES IN MICRO TEACHINGS: IS IT POSSIBLE FOR WEB 2.0 TOOLS TO AFFECT PROSPECTIVE TEACHERS' WEB PEDAGOGICAL CONTENT KNOWLEDGE AND TEACHER SELF-EFFICACY? - Halit Karalar; Bilge Aslan Altan (Informascope, 2018)
The purpose of this study was to determine the effect of Web 2.0 tools applied in microteachings on prospective teachers' web pedagogical content knowledge and teacher self-efficacy, and to examine their views on the procedure. This research used mixed research design and was conducted with 24 prospective teachers who participated in teacher training certificate program in Faculty of Education in a state university in Turkey. Web pedagogical content knowledge scale, teacher self-efficacy scale, and an open-ended question form were used as data collection tools. Paired samples t-test and Pearson correlation analysis were applied for the analysis of quantitative data; content analysis was used to analyze the qualitative data. The findings showed that there was a significant difference on prospective teachers' web pedagogical content knowledge and teacher self-efficacy levels after Web 2.0 tools implementation. The research also concluded that there was a medium level positive relation between teacher candidates' web pedagogical content knowledge and teacher self-efficacy. They stated that it was easy to use these tools, learning was fun, easy, and permanent, and they actively involved in instructional time. They added that they were eager to apply Web 2.0 tools in their future classrooms.